Microbial community in microbial fuel cell (MFC) medium and effluent enriched with purple photosynthetic bacterium (Rhodopseudomonas sp.) - Park, Tae-Jin (Springer, 2014)
High power densities have been obtained from MFC reactors having a purple color characteristic of Rhodopseudomonas. We investigated the microbial community structure and population in developed purple MFC medium (DPMM) and MFC effluent (DPME) using 16S rRNA pyrosequencing. In DPMM, dominant bacteria were Comamonas (44.6%), Rhodopseudomonas (19.5%) and Pseudomonas (17.2%). The bacterial community of DPME mainly consisted of bacteria related to Rhodopseudomonas (72.2%). Hydrogen oxidizing bacteria were identified in both purple-colored samples: Hydrogenophaga and Sphaerochaeta in the DPMM, and Arcobacter, unclassified Ignavibacteriaceae, Acinetobacter, Desulfovibrio and Wolinella in the DPME. The methanogenic community of both purple-colored samples was dominated by hydrogenotrophic methanogens including Methanobacterium, Methanobrevibacter and Methanocorpusculum with significantly lower numbers of Methanosarcina. These results suggeste that hydrogen is actively produced by Rhodopseudomonas that leads to the dominance of hydrogen consuming microorganisms in both purple-colored samples. The syntrophic relationship between Rhodopseudomonas and hydrogenotrophic microbes might be important for producing high power density in the acetate-fed MFC under light conditions.